Development of Test Results and Physical Condition Measurement Methods Using Fitness Applications in Performance Sports - Farit, Al; Hartati, Hartati; Iyakrus, Iyakrus (Journal of Physical Education Health and Sport, 2023)
The research entitled Development of Application-Based Physical Condition Test Results and Measurements in Short Distance Running Athletics, 1) Wants to Make an Application for Processing Test Results and Physical Condition Measurements of Athletes in Athletics Distance Running Numbers. 2) Can find out the results of physical test data processing, which is valid, practical and effective manually or using digital applications on athletic athletes short distance running numbers. The method used in this study is RD, which is a study that describes products in the form of fitness test applications and physical test component instruments applied to athletic athletes in short-distance running numbers. The results of the research conducted were material validation resulting in validity of 85%, language validation of 83% and media validation of 90%. In small-scale trials it produced practicality of 78% and in large-scale trials the level of practicality produced 84.9% and the effectiveness of test results from media applications in the "effective" category with a percentage of 84.9%. From the results of the study, it can be concluded that the development of application-based physical condition test results and measurements in athletic athletes short distance running numbers is valid, practical, and effective. And can be used by coaches, to process data on the results of the physical condition of athletic athletes short distance running numbers,  in order to speed up processing test result data.